Structural Performance of Compacted Earth Block Walls: An Experimental and Numerical Investigation - Abdeltawab, Hady (AUC Knowledge Fountain, 2026)
Compressed Earth Blocks (CEBs) have emerged as a sustainable and low-carbon alternative to conventional masonry blocks, yet their structural limitations, particularly in strength, durability, and interface behavior, remain major constraints for adoption in load-bearing applications. Stabilization using lime and thermoplastic additives has been proposed as means of improving mechanical performance. However, studies that integrate both experimental testing and numerical modeling of stabilized CEB walls are limited. Subsequently, this thesis investigates the structural performance of lime and thermoplastic stabilized earth block walls through a combined experimental and finite element modeling (FEM) approach. The aim of the study is to understand how stabilization enhances wall-level behavior under compressive and combined compressive-lateral loading. The experimental program consisted of three scales of investigation: block-level, prism-level, and wall-level testing. Stabilized CEBs were first produced and evaluated in compression, demonstrating an average compressive strength of approximately 9 MPa, confirming substantial improvement in block integrity due to stabilization. To characterize mortar-block interaction, two prism configurations were tested. Standard compression prisms composed of three blocks with mortar joints, and shear-bond prisms were formulated. Both prism types exhibited premature failure governed by the mortar joints rather than block crushing, highlighting the relatively weak adhesion between cement mortar and stabilized CEB surfaces. The shear-bond prisms showed brittle responses with limited post-peak resistance, suggesting that interface properties may control overall wall behavior even when block strength is high. Moreover, five wall specimens (0.8 m × 0.8 m) were constructed and tested where three walls were tested under axial compression and two under combined compressive–lateral loading. Instrumentation included three LVDTs per wall to monitor vertical, lateral, and out-of-plane displacement. The compressive walls failed at approximately 0.7 MPa, showing also brittle failure initiated at mortar joints, consistent with prism-level observations. Combined loading walls demonstrate notable stiffness degradation and diagonal crack formation, with failure governed by shear sliding and joint debonding rather than block damage.  A detailed finite element model was also developed to replicate the behavior of the test walls where the simulation closely matched the elastic portion of the experimental load-displacement curves, and the predicted ultimate load. The model reproduced the observed failure mechanisms and localized tensile cracking. Finally, a comparative analysis demonstrated that FEM is capable of reliably predicting global response trends, ultimate strength, and crack patterns for stabilized CEB walls. However, accurate modeling of mortar–block interaction remains a critical challenge incorporating interface specific properties, and cohesive zone elements. The findings of this study confirm that lime and thermoplastic blocks stabilization significantly enhance block-level strength, enabling the production of high-quality CEB units suitable for structural applications. However, the overall wall performance is heavily influenced by the mortar interface, which governs failure in both compression and combined loading. The work underscores the need for compatible mortar types, improved interface treatment, and more advanced constitutive modeling of joint behavior. Recommendations for future research include expanding stabilization combinations, new mortar combinations, and refining numerical models with interface calibration. Overall, this thesis contributes a comprehensive experimental-numerical framework for evaluating stabilized earth masonry and provides practical insights for improving construction practices, enhancing structural reliability, and advancing sustainable masonry research.